Islamic interbank money market: a comparative legal study between Malaysia and some notable jurisdictions - Olayemi, Abdul Azeez Maruf; Hasan, Aznan; Ibrahim, Uzaimah; Mohd Yasin, Norhashimah; Buang, Ahmad Hidayat (CLJ Law Network, 2015)
The short term instruments of investment are generally required for the purpose of providing liquidity facilities for banks and other financial institutions to manage the mismatch in their liquidity portfolio. The same thing goes for companies that may be in need of money to pay the salaries of their employees or to meet the mismatch of other unexpected expenditures. The government also demands for liquid facilities at a time to meet its liquidity needs for infrastructural development and concurrent expenditures. Money market facilities are made available to bridge these gaps. The maturity period of the facilities ranges from overnight to one year.1 This article discusses the Islamic interbank money market, its functions and its instruments. It makes a comparison between the leading countries in the practice of Islamic banking. It therefore, proposed the adoption of the Malaysian framework of the market for the other jurisdiction, due to the fact that it is the most developed market in terms of regulations and availability of instruments. The discussion relies on the framework for guidance on the study.